New Equivalence Tests for Hardy–Weinberg Equilibrium and Multiple Alleles - Vladimir Ostrovski (Stats, 2020)
We consider testing equivalence to Hardy−Weinberg Equilibrium in case of multiple alleles. Two different test statistics are proposed for this test problem. The asymptotic distribution of the test statistics is derived. The corresponding tests can be carried out using asymptotic approximation. Alternatively, the variance of the test statistics can be estimated by the bootstrap method. The proposed tests are applied to three real data sets. The finite sample performance of the tests is studied by simulations, which are inspired by the real data sets.